The Effectiveness of Happiness Training on Improving the Quality of Life of Women in Pars Special Economic Zone Staffs Based on Their Religious Attitudes - Dehghani, Farzaneh; Seifi , Mohammad; Nateghi, Faezeh; Faghihi, Alireza (Iranian Journal of Educational Sociology, 2022)
Purpose: The purpose of this study was to investigate the effectiveness of Fordeys Happiness Training on improving the quality of life of women in Pars Special Economic Zone employees according to their religious attitude. Methodology: The research method is semi-experimental with two groups testing using pretest and post-test. The statistical population of this research was all the women who were in the staff of the Pars Special Economic Zone, who, due to the diversity of the community, examined a special block. The number of female housewives in this block was 280, of which 80 were selected through Cochran's formula by simple random sampling and randomly divided into two equal experimental and control groups. After conducting a pre-test of quality of life and religious attitude that based on the results of both test and control groups divided into two strong and weak religious groups, the Happiness Program was performed for 14 sessions of 2 hours for the experimental group and then the test Quality of life was taken from both groups. Findings: Findings show that there is a significant relationship between happiness education and quality of life of women and their religious attitudes. This means that there is a significant difference between the strong and weak religious attitudes group and people with strong religious attitudes have a better quality of life with physical, psychological, social and environmental components than those with a weak religious attitude. Discussion: Happiness is one of the most important human needs, which has a major impact on the formation of personality and mental health.